Caught napping in the time of tropical diseases. Issue 6 (November 2014) - Kissoon, Niranjan; Uyeki, Tim
Abstract : Airline deregulation in 1978 and optimization of routes have been a boon to foreign travel, including to and from Canada, which has one of the fastest growing populations of the G8 countries. Millions of overseas tourists visit Canada each year. More than 20% (almost 7 million) of Canada's population is foreign born, with at least 50% of new immigrants arriving from tropical locales. Recent immigrants may travel to and from their countries of origin.